Preclinical PK investigation of a novel IDO1/TDO dual inhibitor—SHR9146 in mouse plasma and tissues by LC-MS/MS - Xiao, Mei; Zhong, Kan; Guo, Li; Li, Wei; Wang, Xiaoli; Qiu, Zhenjun; Hang, Taijun (Frontiers in Oncology, 2023)
Purpose The aim of the present study was to establish a liquid chromatography–tandem mass spectrometry (LC-MS/MS) method for the determination of SHR9146, a novel IDO1/TDO dual inhibitor, in mouse plasma and tissues, and to apply it to investigate the preclinical plasma pharmacokinetics and tissue distribution of SHR9146 in mice. Methods Samples were spiked with deuterated SHR9146-d4 as an internal standard and pretreated by protein-precipitation extraction with methanol. Chromatographic separation was performed on a Venusil ABS C18 column (150 × 4.6 mm, 5 μm) by isocratic elution with 10 mM ammonium acetate buffer containing 0.1% formic acid solution and methanol as mobile phases. MS detection was conducted in positive electrospray ionization with multiple reaction monitoring at m/z 444.1/229.4 for SHR9146 and m/z 448.4/229.2 for the internal standard. Results The method showed good linearity in the calibration range from 0.05 to 50.0 μg/mL. Precisions (intra- and inter-run) were in the range from 0.5% to 5.1%, and accuracies (RE) were between −3.0% and 4.4% for all the concentration levels. SHR9146 was stable in all the tested bio-samples with recoveries >90%. Pharmacokinetic parameters were obtained by non-compartmental analysis. SHR9146 has a half-life of 0.713 h when IV-injected, with CL 12 mL/min/kg and Vd 0.666 L/kg. After oral dosing from 20 to 80 mg/kg, Cmax (range from 8.751 to 12.893 μg/mL) and AUC0-t (range from 15.606 to 69.971 μg·h/mL) of SHR9146 showed dose proportionality. Other post-oral pharmacokinetic parameters in plasma were as follows (n=6): Tmax 0.79 ± 0.36 h, t1/2 1.586 ± 0.853 h, CL 19.8 ± 0.9 mL/min/kg, Vd 3.427± 1.617 L/kg, and absolute bioavailability of 54.2% ± 12.6% (range from 40.2% to 64.7%). In addition, SHR9146 was found to be absorbed rapidly and distributed widely and mainly in the stomach, adrenal gland, liver, and lung. Conclusion The method was simple, sensitive, accurate, and specific and was successfully applied for the preclinical pharmacokinetic and tissue distribution study of SHR9146 in mice. The results showed that SHR9146 had dose-independent kinetics in mice via oral administration and was absorbed rapidly and distributed widely. The study provides a good basis for further drug development assessment.